ANALISIS KEBERLANJUTAN PT EAST JAKARTA INDUSTRIAL PARK DALAM MEWUJUDKAN KAWASAN INDUSTRI YANG BERWAWASAN LINGKUNGAN - Pien Budiyanto; Asep Saefuddin; Eka Intan Kumala Putri (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2015)
Sustainability analysis of an industrial estate in multidimensional aspects is one of the important steps as an evaluation and review of the operation. Evaluation and review are very useful to evaluate whether the purpose of the existence of an industrial estate follows in PP 4 2009 on environmental procedures. Avoiding this procedures will affect the sustainability of the industrial estate. The Research was carried out in the industrial park EJIP 25-year-old base on ecological dimension economic, social, technological and management criteria for good governance principle. This analysis used Multi Dimensional Scaling (MDS) with techniques of Rapid Appraisal for Industrial Park (Rap Industrial Park). The result of the research showed that status of the sustainability of the industrial estate based on the ecological dimension was quite sustainable. While the perspective of the economic, social, technological and management were obtained good sustainable statusKeywords: Industrial estate, Sustainability, Rap Industrial Park